2016
DOI: 10.1371/journal.pone.0163806
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Vitiligo: A Meta-Analysis

Abstract: ObjectiveTo conduct a meta-analysis assessing the prevalence of vitiligo.MethodsLiteratures that reported prevalence rates of vitiligo were identified using EMBASE, PubMed, the Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang database and Weipu database for the period from inception to May 2016. We performed stratified analyses on possible sources of bias, including areas difference, years of publication, gender and age. Publication bias was assessed with Egger’s test method.ResultsA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
146
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(168 citation statements)
references
References 57 publications
9
146
0
1
Order By: Relevance
“…It has its onset mostly during the 2nd and 3rd decade of life and affects females with a slight predilection over males. Although found globally, vitiligo tends to be more frequent among Asians and Africans (Tarle, Nascimento, Mira, & Castro, 2014;Zhang et al, 2016). In Mexico, a multicentre survey with 50,000 individuals estimated the prevalence to be 0.21% (Estrada Castañón et al, 1992), but data for South America are relatively sparse.…”
Section: Prevalence Of Vitiligo In Brazil-a Population Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…It has its onset mostly during the 2nd and 3rd decade of life and affects females with a slight predilection over males. Although found globally, vitiligo tends to be more frequent among Asians and Africans (Tarle, Nascimento, Mira, & Castro, 2014;Zhang et al, 2016). In Mexico, a multicentre survey with 50,000 individuals estimated the prevalence to be 0.21% (Estrada Castañón et al, 1992), but data for South America are relatively sparse.…”
Section: Prevalence Of Vitiligo In Brazil-a Population Surveymentioning
confidence: 99%
“…It is important to note, however, that prevalence data do not only depend on study population but also on study methodology. For instance, a meta-analysis has shown a pooled prevalence of 1.8% from 22 hospital-based studies but only 0.2% from 82 community-based studies, with the latter showing evidence of publication bias (Zhang et al, 2016).…”
Section: Prevalence Of Vitiligo In Brazil-a Population Surveymentioning
confidence: 99%
“…Indeed, for the management of various skin disorders, the 308‐nm excimer laser has become a common strategy . It has also been revealed that this laser has been used successfully to treat vitiligo …”
Section: Introductionmentioning
confidence: 99%
“…The global vitiligo prevalence varies from 0.004% to 9.98% with an estimate for the United States at 1% of the population, according to a meta‐analysis by Zhang et al (). Previous research on Quality of Life by Teovska Mitrevska, Eleftheriadou, Guarneri (), psycho‐social impact and socio‐economic burden of vitiligo (Lai, Yew, Kennedy, & Schwartz, ), patient's experiences (Picardo et al, ) and self‐reported treatment outcomes (Teasdale et al, ) highlighted further need for research in this area.…”
Section: Introductionmentioning
confidence: 99%